Exploring English grammar - Simon-Vandenbergen, Anne-Marie, 1949- (Leuven : Garant, 2000)
As an introduction to the systematic study of English grammar for advances learners, this book distinguishes itself from the merely practical, pedagogical school grammar on the one hand and the specialized liguistic grammar on the otehr hand. Assuming a basic practical knowledge of the rules of English on the part of the reader, its main concertn is to familiarize the student with grammatical analysis and technical vocabulary such as they are today, thus preparing him or her for a more specialized study of the language. The author has successfully steered a middle course between presenting grammatical issues in their most bewildering complexity and simplifying the subject matter to the extent of distortion. As the average student of English takes a keen interest in British culture in general, and English literature in particular, grammatical description is illustrated with quotes from literature, nursery rhymes and various other sources.